New Product Development based on Web Technology – Case Studies in Brazilian Companies - De Matos, Cláudia Aparecida; Laurindo, Fernando José Barbin (Brazilian Journal of Operations & Production Management, 2010)
The advent of new information and rapid-communication technologies such as extremely powerful desktop computers, the Internet, and the World Wide Web (web) are leading to new and exciting methods of concept evaluation. This paper aims to analyze how companies are exploring Web (Internet) technology for developing new products, based on the concepts of interactivity and connectivity. The adopted methodological approach was case study.Two service companies were studied, selected according to their previous (and preliminary) classification in the Strategic Grid. A plan was developed based on the theoretical background in order to carry out this research. Interviews were made with at least three different professionals (from different areas and hierarchical positions) of each company. Information was collected through semi-structured interviews. The choice of companies of different classification in the Grid is important to analyze the differences and similarities in the new product development process and to allow a comparison among these enterprises. The preliminary results allowed the identification of enablers and tools for supporting the development of a new product as well as the identification of the components that are used during the innovation cycle of creation of a product based on the web.